THE ANALYSIS OF CONVERSATIONAL IMPLICATURE IN “ONWARD” MOVIE - Shindy Faulia Sithiayuki (EL2J (English Language and Literature Journal), 2022)
This study aim to identify the utterances that contain conversational implicature that produce between two characters in Onward movie. In this research the writer analyze the utterances produce by Ian and Barley which contain conversational implicature with the hidden meaning based Grice’s theory. The writer use qualitative method to help while collecting data and analyzing the data. The benefits of used that method in this research is the writer can easily collected the data and analyze the data. The writer use theory from Grice about conversational implicature. The data were collected and analyzed based the maxim and analyze the hidden meaning that produced by Ian and Barley during their conversation in that movie. The result shows that there are fifteen data that contain of conversational implicature found on Onward movie. There are 10 utterances that classified as maxim of quantity, 3 utterances classified as maxim of quality, 1 utterance classified as maxim of manner, and 1 utterance as maxim of relation. The writer also concludes that conversation that occurs in Onward movie contain implied meaning that means Ian, Barley, Bronco, Mom and Ian’s friends always saying the fact, they are answers the question quite informative, relevant with the question and avoid the ambiguity.